Road structure with high mixing amount of modified gold tailings
By incorporating and modifying gold tailings into the road structure, the shortage of gold tailings storage and road construction materials is solved, and efficient utilization of resources and high quality and long life of the road structure are achieved.
Patent Information
- Application Number
- CN202411489845.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-03-04
AI Technical Summary
Gold tailings are stored in large quantities and road construction materials are short of them. It is difficult for the existing technology to effectively utilize gold tailings, resulting in waste of resources and environmental pollution.
By incorporating gold tailings into different levels of the road structure and modifying with admixtures, the high quality and long service life of the road structure layer are ensured. Specifically, it includes the combination of roadbed, pavement base and pavement surface layer, and 80%-95%, 20%-35% and 8%-22% of gold tailings respectively.
It has achieved efficient recycling and utilization of gold tailings, improved the quality and service life of road structures, reduced dependence on natural resources and environmental pollution, and reduced engineering cost.
Smart Images

Figure CN119553562A_ABST
Abstract
Description
[Technical field]
[0001] The invention relates to the technical field of construction waste recycling and highway engineering, and in particular to a high-dosage modified gold tailings road structure. [Background technology]
[0002] The country vigorously advocates the concept of green development and explicitly requires accelerating the supply-side reform of high-emission and high-energy consumption industries to achieve the coordinated development of ecological environment protection and economic growth. Transportation is a key industry for resource consumption and energy emissions, and is listed as one of the three key areas of national energy conservation, emission reduction and climate change response. At present and in the future, my country is still in the process of rapid development of highway construction, and the demand for resources and environmental damage are becoming increasingly prominent. Therefore, how to promote the harmonious coexistence of transportation infrastructure construction and the ecological environment has become an urgent problem to be solved in the road industry.
[0003] Gold tailings refer to the waste residue discharged after the useful target components are extracted from gold ore. According to statistics, the stockpile of gold tailings in my country is more than 200 million tons by 2021, and it is growing at an annual rate of 24.5 million tons, but the utilization rate of gold tailings in the country is only 36.9%. Data show that a large number of gold tailings are idle. Compared with other metal tailings, the original value of gold tailings is relatively low, and the comprehensive recycling rate is also low. The accumulation of a large number of unused tailings not only occupies land resources, but also pollutes the surrounding environment. It is particularly urgent to promote the comprehensive utilization of tailings. On the other hand, the demand for high-quality road engineering materials in highway construction is increasingly strong, especially the consumption of natural stones is very huge. The geometric shape and mechanical properties of gold tailings are similar to those of rolled crushed stone, and they have the potential to replace natural stones. Therefore, incorporating tailings sand into various structural layers of the road to replace natural aggregates, sand and gravel and mineral powder is an effective way to alleviate the contradiction between resource demand and protect the ecological environment.
[0004] The present invention aims to solve the problems of large-scale storage of gold tailings and shortage of road construction materials, explores the resource utilization of gold tailings in road engineering, and aims to provide a road structure combination doped with gold tailings. The method incorporates the gold tailings into the pavement surface layer, pavement base layer and roadbed of the road according to the raw material characteristics of the gold tailings. At the same time, in order to ensure a large doping amount while ensuring the mechanical properties of each structural layer of the road, the gold tailings are modified by an admixture, so as to achieve overall optimization of the comprehensive utilization of gold tailings, maximization of efficiency and maximization of doping amount. [Summary of the invention]
[0005] The technical problem to be solved by the present invention is to provide a high-dosage modified gold tailings road structure, which mixes gold tailings sand into each structural layer of the road, modifies the gold tailings according to the function and material requirements of each structural layer of the road, and ensures that the road structural layer has high quality and long service life.
[0006] The present invention is achieved in that:
[0007] A high-content modified gold tailings road structure, wherein the road structure is provided with a road surface layer, a road base layer and a road subgrade from bottom to top;
[0008] The roadbed thickness is 70-130cm, and the roadbed is made of lime-modified gold tailings mixed evenly and compacted, with the gold tailings content being 80% to 95% and the lime content being 5% to 20%.
[0009] The thickness of the road base is 20-40 cm. The road base is a gold tailings-added cement-stabilized crushed stone base, which is formed by mixing and compacting gold tailings, cement-stabilized crushed stone mixture and admixtures. The gold tailings content is 20%-35%. The cement-stabilized crushed stone mixture includes cement and crushed stone. The admixture of the road base is a mixture of granulated blast furnace slag powder, desulfurized gypsum, lime and polycarboxylic acid high-efficiency water reducing agent. The content of each raw material of the road base is: cement 74kg / m 3 ~123kg / m 3 , gold tailings 490kg / m 3 ~858kg / m 3 , crushed stone 1102kg / m 3 ~1837kg / m 3 , lime 3.67kg / m 3 ~6.13kg / m 3 , granulated blast furnace slag powder 49kg / m 3 ~74kg / m 3 , desulfurized gypsum 3.67kg / m 3 ~6.13kg / m 3 , polycarboxylate high efficiency water reducing agent 0.25kg / m 3 ~2.5kg / m 3 ;
[0010] The thickness of the pavement surface layer is 10 to 30 cm. The pavement surface layer is a modified gold tailings cement concrete surface layer, which is formed by mixing gold tailings, cement concrete mixture and activator, and curing and hardening them uniformly. The gold tailings content is 8%-22%. The cement concrete mixture includes cement, natural sand and gravel; the modified gold tailings cement concrete surface layer activator is composed of fly ash, desulfurized gypsum and water reducing agent; the content of each raw material of the modified gold tailings cement concrete surface layer is as follows: cement 356kg / m 3 ~425kg / m 3 , gold tailings 120kg / m 3 ~200kg / m 3 , crushed stone 1060kg / m 3~1200kg / m 3 , fly ash 80kg / m 3 ~150kg / m 3 , desulfurized gypsum 3kg / m 3 ~6kg / m 3 Polycarboxylate high efficiency water reducing agent 1.0kg / m 3 ~2.0kg / m 3 .
[0011] Furthermore, the grade of granulated blast furnace slag powder in the pavement base admixture is S95 or above; the standard consistency of desulfurized gypsum is ≥60%, the lime is quicklime, and its CaO content is not less than 90%; the water reduction rate of polycarboxylic acid high-efficiency water reducer is ≥25%.
[0012] Furthermore, the gold tailings have a particle size of less than 4.75 mm, and the content of particles with a size of 1.18 to 0.15 mm is not less than 65%.
[0013] Furthermore, the crushed stone in the gold tailings-added cement-stabilized crushed stone base layer is divided into four grades, namely 2.36-4.75 mm, 4.75-9.5 mm, 9.5-19 mm and 19-31.5 mm.
[0014] Furthermore, the grade of fly ash in the modified gold tailings cement concrete surface layer activator is level 2, the standard consistency of desulfurized gypsum is ≥60%, and the water reduction rate of polycarboxylic acid high-efficiency water reducing agent is ≥25%.
[0015] Furthermore, the stones of the road surface layer are granite crushed stone particles, and are crushed stones with three grades: 4.75-9.5 mm, 9.5-19 mm and 19-31.5 mm.
[0016] The present invention has the following advantages:
[0017] The pavement surface layer of the present invention uses gold tailings instead of mineral powder and machine-made sand, the pavement base layer uses gold tailings mixed in a certain proportion, and the roadbed uses lime to improve the gold tailings to ensure the strength and stability of the roadbed. The present invention uses the gold tailings to the best effect according to the functions and material requirements of each structural layer of the road, ensuring that the road structural layer has high quality and a long service life.
[0018] The present invention adds gold tailings to the road structure surface layer, base layer and roadbed, with the addition amounts being 8%-22%, 20%-35% and 80%-95% respectively, so as to maximize the recycling of gold tailings in road engineering and improve the recycling rate of gold tailings. With the increasing shortage of sand and gravel materials, gold tailings are used as substitutes to solve the problem of the whereabouts of industrial waste materials, reduce energy and resource consumption, protect the ecological environment, and reduce engineering costs.
Brief Description of the Drawings
[0019] The present invention will be further described below in conjunction with embodiments with reference to the accompanying drawings.
[0020] Figure 1 Schematic diagram of the particle size distribution of gold tailings in an embodiment of the present invention.
[0021] Figure 2 4 is a dry density and moisture content curve of an embodiment of the present invention.
[0022] Figure 3 4 is a CBR and compaction degree curve diagram of an embodiment of the present invention.
[0023] Figure 4 It is a curve diagram of moisture content and dry density of the modified gold tailings cement stabilized gravel base in the embodiment of the present invention. [Specific implementation method]
[0024] The following will be combined with the attached Figure 1-4 The technical scheme of the present invention is clearly and completely described in detail with specific embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.
[0025] Example 1
[0026] 1. Roadbed:
[0027] 1. Test materials
[0028] (1) Gold tailings
[0029] The gold tailings used in the test are mainly solid wastes discarded by Dayuan Mining Co., Ltd. after gold ore is beneficiated by ball milling and flotation process or after gold or other useful components are recovered by gold extraction process. Its chemical composition and particle size distribution are shown in Table 1. Figure 1 .
[0030] Table 1 Chemical composition of tailings (%)
[0031] <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> <![CDATA[K 2 The]]> <![CDATA[Fe 2 THE 3 ]]> <![CDATA[Na 2 The]]> CaO <![CDATA[ZrO 2 ]]> <![CDATA[Cr 2 THE 3 ]]> <![CDATA[Rb 2 The]]> ZnO other 73.5 13.2 4.0 5.2 2.06 0.6 0.01 0.03 0.02 0.01 1.59
[0032] (2) Lime
[0033] The lime used in the test was produced in Fuzhou, Fujian, and its performance indicators are shown in Table 3.
[0034] Table 3 Lime performance indicators
[0035]
[0036] 2. Experiment
[0037] (1) The lime-modified gold tailings roadbed comprises the following components by weight: gold tailings 1990-2210 kg / m 3 , lime 126kg / m 3 ~210kg / m 3 、Water 168kg / m 3 ~230kg / m 3 .
[0038] (2) Mix the above materials evenly, formulate the test methods and procedures in accordance with the "Highway Geotechnical Test Code" (JTG 3430-2020), and determine the liquid limit, plastic limit, optimum moisture content, maximum dry density and bearing ratio of the roadbed filling material.
[0039] (3) Liquid and plastic limit test:
[0040] (a) Air-dry the above materials, crush them and pass them through a 0.5 mm sieve. Take more than 200 g of the sample under the sieve and divide them into three groups, respectively controlling the moisture content at the liquid limit (point a), slightly above the plastic limit (point c) and the intermediate state between the two (point b). After uniform mixing, let it stand for more than 18 hours.
[0041] (b) Place the prepared samples in layers into a container, compact and level them, and use a moisture content meter to measure the average moisture content.
[0042] (c) Change the contact position and measure the moisture content and average moisture content again.
[0043] (d) Repeat the above steps for the other two groups of samples.
[0044] The specific liquid and plastic limit test results are shown in Table 4 below:
[0045] Table 4 shows the results of the liquid and plastic limit tests.
[0046]
[0047] (4) Compaction test
[0048] (a) Determine the initial moisture content: Prepare 5 samples with an initial moisture content of 5%. Subsequent samples are added with 2% moisture.
[0049] (b) Material preparation: In order to facilitate the calculation of the amount of water to be added for compaction, the test materials should be fully dried and cooled in advance.
[0050] (c) Weighing: The mass of a sample is generally 5.5 kg (the mass of graded crushed stone aggregate can be calculated based on the grade composition and the mass of each grade of material in a sample).
[0051] (d) Preparation of samples: Place a weighed portion of sample on a stainless steel basin and use a spatula to mix the sample thoroughly until it is uniform (calculate the cement content of a sample based on the cement dosage of 5500g of graded crushed stone aggregate. When calculating, pay attention to the difference between the external and internal cement admixture methods. Place a weighed portion of sample on a stainless steel basin and then add the calculated cement. First, mix the cement and aggregate thoroughly. Then, evenly spray the calculated water to be added to the sample on the sample and use a spatula to mix the sample thoroughly until it is uniform.).
[0052] (e) Compacting: The prepared sample (cement stabilized crushed stone, no need to stew the material) shall be immediately subjected to compaction test, and the compaction process shall be carried out in accordance with the provisions of "T0804-94 Test Procedure for Stabilized Materials of Inorganic Binders for Highway Engineering". In order to meet the requirement that each layer is 1 / 3 of the height of the cylinder (1mm-2mm) after compaction, the material added for each layer shall be between 1650g and 1700g. In addition, during the compaction process, due to the impact and vibration of the compaction hammer, the sleeve ring on the test cylinder is easy to loosen and fall off, so attention should be paid to tightening the sleeve at any time.
[0053] (f) Demolding: After the sample is compacted, it is required to scrape the sample flat to the top of the cylinder. After the sample is scraped and cleaned, weigh the cylinder and wet the sample. The accuracy is 5g. Then demold and measure the moisture content of the sample after compaction. Operate according to the provisions of "T0804-94 Test Procedure for Stabilized Materials of Inorganic Binders for Highway Engineering".
[0054] (g) Based on the previous compaction results, change the moisture content (i.e., assuming that the moisture added before compaction will not be lost, estimate the dry density so that the moisture content and dry density can approximately form a hump curve) and repeat the above test steps (d) to (f).
[0055] (h) Calculate the dry density of the sample according to the dry density calculation formula. With dry density as the ordinate and moisture content as the abscissa, draw a curve of dry density and moisture content on the graph, and find the peak point of the curve. The corresponding moisture content is the optimal moisture content, and the corresponding dry density is the maximum dry density.
[0056] The compaction test results are shown in Figure 2 , Table 5 shows the maximum dry density and optimum moisture content
[0057] Table 5 Maximum dry density and optimum moisture content
[0058] <![CDATA[Maximum dry density (g / cm 3 )]]> Optimum moisture content (%) 1.98 11.6
[0059] (5) Load ratio test
[0060] (a) Select representative samples and air-dry them, then measure their air-dried moisture content. Calculate the amount of water to be added based on the sample's optimum moisture content and air-dried moisture content, and evenly spray it on the sample, then mix it evenly and let it stand for 12 hours.
[0061] (b) Weigh the mass of the test tube and the specimen, and prepare the specimen according to the compaction test method, with 3 specimens prepared in each group. Install the specimen on a porous plate with an adjustment rod, add a load plate, put it in a water tank (without adding water for the time being), tighten the mold with a pull rod, install a dial indicator and record the initial reading; add water to the top of the specimen and keep the water level 25mm above the top of the specimen, and record the final reading after soaking in water for 96 hours; remove the specimen, drain the water on the top, let it stand for 15 minutes, remove the load and porous plate, and weigh the mass of the test tube and specimen after soaking in water.
[0062] (c) Carry out penetration test. Place the soaked specimen on the pavement strength tester. Adjust the ball seat to ensure that the penetration rod fully contacts the specimen. Apply gradually increasing load and record the load values at different penetration amounts. The total penetration amount should exceed 6 mm.
[0063] (d) Draw the relationship curve between unit pressure and penetration according to the unit pressure and penetration. According to the bearing ratio calculation formula, calculate the bearing ratio when the penetration is 2.5mm and 5mm, and take the larger value as the bearing ratio of the material. The specific bearing ratio test results are shown in Table 6, and the relationship curve between CBR and compaction degree is shown in Figure 3 .
[0064] Table 6 Load ratio test results
[0065]
[0066] 2. Modified gold tailings cement stabilized gravel base
[0067] 1. Test materials
[0068] (1) Gold tailings are the same as above;
[0069] (2) Cement:
[0070] The P·O 42.5 grade cement purchased from the market was used in the test. Its main technical indicators are shown in Table 7. All performance indicators are in line with the requirements of national standards.
[0071] Table 7 Physical properties of cement
[0072]
[0073]
[0074] (3) Gravel:
[0075] The stone used in this test is granite crushed stone particles. There are four graded crushed stones: 2.36-4.75mm, 4.75-9.5mm, 9.5-19mm, and 19-31.5mm. The needle-like particle content, crushing value index and other quality of the stone used must meet the basic requirements of the relevant industry standard JGJ 52-2006 "Standard for the quality and inspection methods of sand and stone for ordinary concrete".
[0076] (4) Additives
[0077] In this experiment, admixtures purchased from the market were used. Their main categories and indicators are shown in Table 8.
[0078] Table 8 Admixture Index
[0079]
[0080] 2. Experiment
[0081] The modified gold tailings cement stabilized crushed stone base is composed of the following raw materials: cement 74kg / m 3 ~123kg / m 3 , gold tailings 490kg / m 3 ~858kg / m 3 , crushed stone 1102kg / m 3 ~1837kg / m 3 , lime 3.67kg / m 3 ~6.13kg / m 3 , granulated blast furnace slag powder 49kg / m 3 ~74kg / m 3 , desulfurized gypsum 3.67kg / m 3 ~6.13kg / m 3 , polycarboxylate high efficiency water reducing agent 0.25kg / m 3 ~2.5kg / m 3
[0082] The following test was carried out with reference to the relevant test provisions of "Test Procedure for Inorganic Binder Stabilized Materials for Highway Engineering" (JTG E512009).
[0083] (1) Compaction test
[0084] The experimental steps are shown in the roadbed section; the compaction test results are shown in Table 9 below.
[0085] Table 9 Moisture content-dry density
[0086]
[0087]
[0088] (2) Unconfined compressive strength test
[0089] (a) Crush a representative air-dried sample (if necessary, it can be dried in a 50°C oven) with a wooden hammer or a wooden roller, but avoid destroying the original particle size of the particles. Sieve the soil according to the largest sieve of the nominal maximum particle size and classify it.
[0090] (b) One day before the scheduled test, take a representative sample and determine its air-dried moisture content. The sample should be no less than 2000g.
[0091] (c) Weigh a certain amount of air-dried soil, the mass of which varies with the size of the specimen. For a 150 mm x 150 mm specimen, approximately 5700 to 6000 g of dry soil is required for one specimen.
[0092] (d) Based on the compaction results and the mix ratio of the inorganic binder, calculate the amount of water added to each portion of material and the mass of the inorganic binder according to formula (T0843-1).
[0093] (e) Place the weighed soil in a rectangular dish (about 400mm×600mm×70mm). Add water to the soil and mix and simmer. For cement-stabilized materials, the amount of water added should be 1% to 2% less than the optimum water content. (The soaking time is required to be 2 hours. The soaking time is generally not more than 24 hours.)
[0094] (f) Add the predetermined amount of cement and mix well within 1 hour before the specimen is formed. During the mixing process, the reserved water (1% to 2% for cement stabilized materials) should be added to the soil to make the mixture reach the optimal water content. (The mixture with cement added should be made into specimens within 1 hour according to the following method. The mixture that exceeds 1 hour should be discarded.)
[0095] (g) Use a reaction frame and hydraulic jack, or use a pressure test mechanism. Place the lower pad that matches the test mold into the lower part of the test mold, but leave it exposed by about 2 cm. Pour the weighed and specified amount of the stabilizing material mixture into the test mold in 2 to 3 times, and use a tamping rod to gently and evenly compact it after each pouring. Then place the upper pad that matches the test mold into the test mold, and leave it exposed by about 2 cm (that is, the upper and lower pads should be exposed to the outside of the test mold The parts should be equal.
[0096] (h) Place the entire test mold (together with the upper and lower pads) on the jack in the reaction frame (a flat ball seat should be placed under the jack) or on a press, and apply pressure at a loading rate of 1 mm / min until the upper and lower pressure columns are pressed into the test mold, and maintain the pressure for 2 minutes.
[0097] (i) After releasing the pressure, remove the test mold and place it on the demoulding device to eject the specimen. When using cement to stabilize non-cohesive fine-grained soil, it is best to wait 2 to 4 hours before demoulding;
[0098] (j) Weigh the mass of the specimen as m, with a large specimen accurate to 0.1 g. Then use a vernier caliper to measure the specimen height h, accurate to 0.1 mm. Check the specimen height and mass, and treat any specimen that does not meet the molding standard as scrap.
[0099] (k) After weighing, the specimens should be immediately sealed in plastic bags, covered with damp towels, and moved to the curing room. The successfully demoulded specimens should be wrapped in plastic bags to prevent the loss of water in the specimens, and placed in a standard curing box for curing for 6 days. The curing temperature is 20℃±2℃, and the curing humidity of the specimens should not be less than 95%. On the last day, the specimens should be immersed in water with the water level 2.5cm above the surface of the specimens.
[0100] (l) Take the specimen that has been immersed in water for one day and one night out of the water, absorb the water on the surface of the specimen with a soft cloth, and weigh the mass of the specimen. Use a vernier caliper to measure the height of the specimen with an accuracy of 0.1 mm.
[0101] (m) Place the specimen on a pavement material strength tester or press, and place a flat ball seat on the lifting platform to conduct a compression test. During the test, the loading rate should be maintained at 1mm / min. Record the maximum pressure P (N) when the specimen fails.
[0102] (n) Take a representative sample from the inside of the test piece (after breaking it) and determine its moisture content w according to the method in this specification T0801-2009.
[0103] (o) Calculation:
[0104] The unconfined compressive strength of the specimen is calculated as follows:
[0105] Rc=P / A Formula 1;
[0106]
[0107] Where: Rc is the unconfined compressive strength of the specimen (MPa), P is the maximum pressure when the specimen is damaged (N); A is the cross-sectional area of the specimen (mm 2 ); D is the diameter of the specimen (mm).
[0108] The unconfined compressive strength test results are shown in Table 10 below:
[0109] Table 10 Unconfined compressive strength of modified gold tailings cement stabilized crushed stone base at 7 days
[0110]
[0111]
[0112] 3. Modified gold tailings cement concrete surface layer
[0113] 1. Test materials
[0114] (1) Gold tailings are the same as above.
[0115] (2) Cement: Same as above.
[0116] (3) Fly ash:
[0117] The test used Class I fly ash purchased from the market. Its main technical indicators are shown in Table 11. All performance indicators are in compliance with the national standard "Fly ash used in cement and concrete" GB / T1596-2017.
[0118] Table 11 Main technical indicators of fly ash
[0119] Density / (g / cm3) Loss on ignition / % Water demand ratio / % 45μm sieve residue / % Activity index / % 2.30 0.5 94 10 80
[0120] (4)Natural sand
[0121] This test uses Chinese ISO standard sand purchased from the market, which meets the basic requirements of the relevant industry standard JGJ52-2006 "Standard for Quality and Inspection Methods of Sand and Stone for Ordinary Concrete".
[0122] (5) Stone
[0123] The stone used in this test is granite crushed stone particles. There are three grades of crushed stone: 4.75-9.5mm, 9.5-19mm, and 19-31.5mm. The needle-like particle content, crushing value index and other quality of the stone used must meet the basic requirements of the relevant industry standard JGJ 52-2006 "Standard for the quality and inspection methods of sand and stone for ordinary concrete".
[0124] (6) Water
[0125] The mixing water used in this test was tap water.
[0126] (7) The specific components of the admixture are shown in Table 12 below:
[0127] Table 12 Admixture components
[0128]
[0129] 2. Experiment
[0130] The modified gold tailings cement concrete surface layer is composed of the following raw materials: cement 356kg / m 3 ~425kg / m 3 , gold tailings 120kg / m 3 ~200kg / m 3 , crushed stone 1060kg / m 3 ~1200kg / m 3 , fly ash 80kg / m3 ~150kg / m 3 , desulfurized gypsum 3kg / m 3 ~6kg / m 3 , polycarboxylate high efficiency water reducing agent 1.0kg / m 3 ~2.0kg / m 3 .
[0131] Conduct the following test in accordance with the Standard Test Methods for Physical and Mechanical Properties of Ordinary Concrete.
[0132] (1) Compressive strength test
[0133] (a) weighing the raw materials according to the mix ratio determined above;
[0134] (b) Mix the weighed raw materials, first dry mix the cementitious material and fine aggregate, then add the admixture and mix, then add the gravel and continue dry mixing to ensure that the materials are in even contact. Finally, add water and continue stirring to make the gravel and mortar evenly mixed;
[0135] (c) Place the prepared concrete into a standard test piece of 150 mm × 150 mm × 150 mm and place it on a vibration table for compaction.
[0136] (d) Ensure the surface is smooth when concrete is placed in the formwork;
[0137] (e) After curing to the age according to relevant specifications and test requirements, the test pieces to be inspected are taken out and inspected for appearance damage. The most damaged test pieces are taken out and a new set of test pieces is made to ensure the validity of the data;
[0138] (f) Place the test pieces with less or no appearance damage according to their numbers and prepare for pressure testing;
[0139] (c) During the test, the side surface of the specimen should be used as the load-bearing surface;
[0140] (d) Design the loading speed according to the strength grade of concrete. This test is C30, so the loading speed should be between 0.5 and 0.8 MPa / s. During the compression process of the specimen, record the damage changes and corresponding data of the specimen;
[0141] (e) The compressive strength data is calculated according to the following formula:
[0142]
[0143] Where: is the tail f cu Mine concrete specimen compressive strength (MPa), accurate to 0.1MPa; F is the tailings concrete specimen failure load (N); A A is the pressure bearing area of tailings concrete specimen (mm 2);
[0144] (f) In order to reduce the test error, the measured strength values of the three tailings concretes were averaged as the final strength value. The specific compression test results are shown in Table 13:
[0145] Table 13 Compressive strength of modified gold tailings cement concrete
[0146]
[0147] In summary, the present invention has the following advantages:
[0148] (1) Traditional road construction usually relies on natural resources such as sand and gravel, while the present invention uses a large amount of gold tailings as an alternative material to achieve comprehensive utilization of solid waste resources. This not only reduces dependence on natural resources, but also effectively alleviates the pressure of solid waste treatment, while helping to reduce environmental pollution and ecological damage, and helps to achieve green and sustainable road construction.
[0149] (2) Using admixtures to modify gold tailings can improve their physical and mechanical properties and enhance their adhesion and stability with other road structural materials. This can effectively improve the road's bearing capacity, durability and impact resistance, extend the road's service life, and reduce maintenance costs.
[0150] (3) Gold tailings, as a waste resource, are efficiently utilized in the present invention, which helps promote the development of the comprehensive utilization industry of solid waste resources. Through technological innovation and resource recycling, it can provide new development opportunities for related industries and promote economic transformation and upgrading.
[0151] Although the specific implementation modes of the present invention are described above, those skilled in the art should understand that the specific implementation modes described are only illustrative and are not intended to limit the scope of the present invention. Equivalent modifications and changes made by those skilled in the art in accordance with the spirit of the present invention should be included in the scope of protection of the claims of the present invention.
Claims
1. A high-dosage modified gold tailings road structure, characterized by: The road structure is provided with a road surface layer, a road base layer and a road subgrade from bottom to top; The roadbed thickness is 70-130cm, and the roadbed is made of lime-modified gold tailings mixed evenly and compacted, with the gold tailings content being 80% to 95% and the lime content being 5% to 20%. The thickness of the road base is 20-40 cm. The road base is a gold tailings-added cement-stabilized gravel base, which is formed by mixing and compacting the gold tailings, cement-stabilized gravel mixture and admixtures. The components of the cement-stabilized gravel mixture include cement and gravel. The admixture of the road base is a mixture of granulated blast furnace slag powder, desulfurized gypsum, lime and polycarboxylic acid high-efficiency water reducing agent. The content of each raw material of the road base is: cement 74 kg / m 3 ~123kg / m 3 , gold tailings 490kg / m 3 ~858kg / m 3 , crushed stone 1102kg / m 3 ~1837kg / m 3 , lime 3.67kg / m 3 ~6.13kg / m 3 , granulated blast furnace slag powder 49kg / m 3 ~74kg / m 3 , desulfurized gypsum 3.67kg / m 3 ~6.13kg / m 3 , polycarboxylate high efficiency water reducing agent 0.25kg / m 3 ~2.5kg / m 3 ; The thickness of the road surface layer is 10 to 30 cm. The road surface layer is a modified gold tailings cement concrete surface layer, which is formed by mixing gold tailings, cement concrete mixture and activator, and curing and hardening them evenly. The cement concrete mixture includes cement, natural sand and gravel; the modified gold tailings cement concrete surface layer activator is composed of fly ash, desulfurized gypsum and water reducing agent; the content of each raw material of the modified gold tailings cement concrete surface layer is as follows: cement 356kg / m 3 ~425kg / m 3 , gold tailings 120kg / m 3 ~200kg / m 3 , crushed stone 1060kg / m 3 ~1200kg / m 3 , fly ash 80kg / m 3 ~150kg / m 3 , desulfurized gypsum 3kg / m 3 ~6kg / m 3 , polycarboxylate high efficiency water reducing agent 1.0kg / m 3 ~2.0kg / m 3 .
2. A modified gold tailings road structure according to claim 1, characterized in that: The grade of the granulated blast furnace slag powder in the road base admixture is S95 or above; the standard consistency of the desulfurized gypsum is ≥60%; the lime is quicklime, and its CaO content is not less than 90%; the water reduction rate of the polycarboxylic acid high-efficiency water reducing agent is ≥25%.
3. A high-dosage modified gold tailings road structure according to claim 1, characterized in that: The particle size of the gold tailings is less than 4.75 mm, and the content of particles with a diameter of 1.18 to 0.15 mm is not less than 65%.
4. A high-dosage modified gold tailings road structure according to claim 1, characterized in that: The crushed stones in the gold tailings-added cement-stabilized crushed stone base are divided into four grades, namely 2.36-4.75 mm, 4.75-9.5 mm, 9.5-19 mm and 19-31.5 mm.
5. The high-dosage modified gold tailings road structure according to claim 1 is characterized in that: The grade of fly ash in the modified gold tailings cement concrete surface layer activator is grade II, the standard consistency of desulfurized gypsum is ≥60%, and the water reduction rate of polycarboxylic acid high-efficiency water reducing agent is ≥25%.
6. A high-dosage modified gold tailings road structure according to claim 1, characterized in that: The stones of the road surface layer are granite crushed stone particles, and are crushed stones of three grades: 4.75-9.5 mm, 9.5-19 mm and 19-31.5 mm.